Effectiveness of peer-led health behaviour interventions on adolescent’s mental health and wellbeing: a systematic review and meta-analysis - Jacinta Brinsley; Matthew Schmidt; Rachel Curtis; Catherine EM Simpson; Jessica Edwards; Emily E. Eglitis; Georgia Gosse; Michael Broad; Bryony Jardine; Elizabeth Taddeo; Prerna Banati; Carol Maher (Scientific Reports)
Abstract Mental health disorders affect 15% of youth aged 10–19 years globally, typically emerging before age 15. While school-based peer-led programs show promise in improving physical health behaviours by leveraging existing social networks, reducing stigma, and demonstrating high implementation feasibility, their effectiveness for mental health outcomes remains unclear. This systematic review examined controlled trials of school-based, peer-led lifestyle interventions (physical activity, diet, or sleep) reporting mental health outcomes in adolescents aged 10–19 years. Six electronic databases were searched up to March 28, 2024. Seven studies met inclusion criteria, encompassing 7,060 adolescents from 151 schools across the UK, USA, Canada, and Norway. Interventions varied in frequency and duration, with six focusing on physical activity and one on diet. Meta-analyses revealed no significant effects for psychological difficulties (MD = 0.60, 95% CI -3.52 to 4.72; p = 0.32, k = 2), self-efficacy for physical activity (SMD = 0.18, 95% CI -3.08 to 3.44; p = 0.61, k = 2), or wellbeing (SMD = 0.0, 95% CI -2.94 to 2.94; p = 1.0, k = 2). These findings, while requiring cautious interpretation, highlight the pressing need for more comprehensive and rigorous research to better understand the impact of peer-led interventions on mental health outcomes.